Composite brazing filler metal and preparation method thereof

By using composite solder materials in soldering technology, including tin-silver copper alloy powder and metal particles, the problem of welding joint melting during multiple welding is solved, the welding reliability and melting point of solder joints are improved, and the risk of part drops is reduced .

CN119237987APending Publication Date: 2025-01-03ZTE CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310807484.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the 3D packaging process, when soldering multiple weldings in soldering technology, the solder at the formed solder joints will melt again, resulting in low welding reliability and the packaging of the entire package cannot be effectively completed.

Method used

Compound solder materials, including tin-silver copper alloy powder and metal particles, are used to remove the surface oxide film of the metal particles and mix them with tin-silver copper alloy powder to form composite solder powder and mix them with the solder to improve welding reliability.

Benefits of technology

The metallurgical reaction is used to form interfacial metal co-deposited substances, which significantly improves the melting point of the solder joints, reduces the risk of part loss, and improves the welding reliability in multiple welding processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237987A_ABST
    Figure CN119237987A_ABST
Patent Text Reader

Abstract

The invention discloses brazing filler metal and a preparation method thereof. The brazing filler metal comprises composite brazing filler metal powder and soft brazing flux. Wherein the composite brazing filler metal powder comprises the following components in percentage by mass: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles. The composite brazing filler metal at the welding spot is strengthened in the first welding process through the metal particles, the melting point of the composite brazing filler metal at the welding spot after the first welding is improved, and therefore the composite brazing filler metal at the welding spot formed by the first welding can be prevented from being melted in the second welding process, the part falling risk can be reduced, and the welding reliability of the brazing filler metal is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of soft soldering, and in particular to a composite solder and a preparation method thereof. Background Art

[0002] With the rapid development of 3D (3-dimension) packaging technology, the assembly density of electronic products is getting higher and higher, and the packaging process is becoming more and more complicated. The packaging of electronic products usually adopts the method of soldering. At present, in the process of packaging by soldering, it is difficult to complete the packaging of the entire package body by one welding. Multiple welding has become a packaging process commonly used in 3D packaging. However, in the process of multiple welding, after the material is soldered to the substrate by the solder, when other materials are soldered again, the solder at the formed solder joint will melt again, causing the material connected by the solder joint to fall off, and the welding reliability is low. Summary of the invention

[0003] The main purpose of the present application is to provide a composite solder and a preparation method thereof, aiming to solve the technical problem of low welding reliability of the solder in multiple welding processes in conventional technology.

[0004] To achieve the above-mentioned purpose, the embodiment of the present application provides a composite solder, wherein the composite solder comprises composite solder powder and a solder flux;

[0005] The composite solder powder comprises the following components in terms of mass percentage: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles.

[0006] The present application also provides a method for preparing a composite solder, which is used to prepare the composite solder as described above. The method for preparing the composite solder comprises the following steps:

[0007] Remove the oxide film on the surface of metal particles;

[0008] The metal particles after the oxide film is removed are mixed and kneaded with tin-silver-copper alloy powder to obtain composite solder powder;

[0009] The composite solder powder is mixed with a soft solder agent to obtain a composite solder.

[0010] The embodiment of the present application discloses a composite solder, which includes composite solder powder and solder flux; wherein the composite solder powder includes the following components in terms of mass percentage: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles. During the first welding process, the metal particles in the composite solder at the solder joint formed by the first welding react metallurgically with the tin-silver-copper alloy powder to form an interface metal compound, and the grain boundary is strengthened, resulting in a significant strengthening effect. Therefore, after the first welding, the melting point of the composite solder at the solder joint formed by the first welding is greatly improved; on the other hand, the appropriate mass proportion of metal particles can improve welding reliability, the mass proportion of metal particles is small, the strengthening effect is small, and the improvement of melting point is not obvious, the mass proportion of metal particles is large, the metal particles are difficult to disperse, the bonding tightness between the metal particles and the tin-silver-copper alloy powder is reduced, and impurities are formed, which will lead to the deterioration of the uniformity of the composite solder and the reduction of welding quality. Therefore, it is determined that the mass proportion of the metal particles in the composite solder is 0.5%-20%. In this way, the melting point of the composite solder after adding metal particles accounting for 0.5%-20% by mass in the composite solder can change after one melting, increasing by about 17-39°C. In this way, during the second welding process, the composite solder at the weld point formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 A schematic diagram of a first reflow soldering scenario involved in an embodiment of the present application;

[0012] Figure 2 A schematic diagram of a second reflow soldering scenario involved in an embodiment of the present application;

[0013] Figure 3 It is a schematic flow chart of a method for preparing a composite solder according to an embodiment of the present application.

[0014] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0015] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0016] With the rapid development of 3D packaging technology, the assembly density of electronic products is getting higher and higher, and the packaging process is becoming more and more complicated. The packaging of electronic products usually adopts the method of soft soldering. At present, in the process of packaging by soft soldering, it is difficult to complete the packaging of the entire package body through one welding. Multiple welding has become a commonly used packaging process for 3D packaging. For example, wafer-level chip packaging usually requires 2-3 times of reflow soldering, or even more times of reflow soldering. However, in the process of multiple welding, after the material is soldered to the substrate with solder, when other materials are soldered again, the solder at the formed solder joint will melt again when the temperature rises to the melting point, causing the material connected by the solder joint to fall off, and the welding reliability is low. For example, refer to Figure 1 and Figure 2 , Figure 1 This is a schematic diagram of the first reflow soldering scenario involved in the embodiment of the present application. Figure 2 This is a schematic diagram of the second reflow soldering scenario involved in the embodiment of the present application. Figure 1 and Figure 2 The PCB (Printed Circuit Board) 10 shown in the figure includes a first surface 11 and a second surface 12 on which components need to be soldered, and the first surface 11 and the second surface 12 are arranged opposite to each other. During the first reflow soldering, the first surface 11 of the PCB 10 is placed upward, and then the first component 21 is soldered to the first surface 11 of the PCB 10 through the solder 30. After the first component 21 is soldered to the first surface 11 of the PCB 10, if it is necessary to solder the second component 22 to the second surface 12 of the PCB 10 through secondary soldering, the PCB 10 needs to be turned over together with the first component 21 soldered on the first surface 11, so that the second surface 12 faces upward, and then the second component 22 is soldered to the second surface 12 of the PCB 10 through the solder 30. However, during the process of soldering the second component 22, the soldering temperature will reach the melting point of the solder 30, so that the solder 30 between the first component 21 and the first surface 11 will melt, causing the first component 21 to fall off. It can be seen from this that when using soft soldering to weld materials with different surfaces, the subsequent welding process will cause the solder at the previously formed solder joint to melt, resulting in the risk of the previously welded material falling off, and the welding reliability is greatly reduced.

[0017] In order to solve the above technical problems, the embodiment of the present application provides a composite solder, which includes composite solder powder and a solder flux;

[0018] The composite solder powder comprises the following components in terms of mass percentage: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles.

[0019] In this embodiment, the composite solder is used for soft soldering. Soft soldering refers to a connection method using a solder with a melting point not exceeding 450°C and heating to a soldering temperature lower than the melting point of the base material but higher than the melting point of the solder to achieve connection.

[0020] Composite solder refers to a solder composed of tin-silver-copper alloy powder and metal particles. The composite solder includes composite solder powder and soft solder flux. The soft solder flux refers to a substance that can melt to form slag and / or gas during the soft soldering process, and protects the molten metal and has metallurgical physical and chemical effects. It can be used to remove oxides on the surface of the base material and the solder, protect the base material and the solder, etc. The soft solder flux contains at least one component selected from inorganic acids, organic acids and ammonium salts, and may also contain at least one component selected from activators, solvents, diluents, fluxes, etc. For example, it may be rosin, amines, organic halides, solder flux with a brand name of RJ1, solder flux with a brand name of RJ3, solder flux with a brand name of RJ5, solder flux with a brand name of RJ8, etc. The soft solder flux can be purchased as a commercially available product or configured by itself, and this embodiment does not impose any restrictions on this.

[0021] Exemplarily, the mass proportion of the composite solder powder in the composite solder is 85%-93%, and the mass proportion of the solder flux in the composite solder is 7%-15%.

[0022] If the mass proportion of the solder flux in the composite solder is too low, the wettability and spreading performance of the composite solder are poor. During the soldering process, pores may appear due to the inability to spread out due to accumulation, resulting in reduced welding quality. It may also make the composite solder have poor performance in removing surface oxides, resulting in low welding bonding strength and reduced welding quality. If the mass proportion of the solder flux in the composite solder is too high, pores may appear due to the uneven distribution of the composite solder powder and the inability to completely fill it, and the welding time is long. Excessive solder flux may also remain, resulting in poor electrical properties. Therefore, it is determined that the mass proportion of the composite solder powder in the composite solder is 85%-93%, and the mass proportion of the solder flux in the composite solder is 7%-15%. For example, the composite solder may include 85wt% of the composite solder powder and 15wt% of the solder flux, or the composite solder may include 90wt% of the composite solder powder and 10wt% of the solder flux, or the composite solder may include 93wt% of the composite solder powder and 7wt% of the solder flux.

[0023] The composite solder powder includes tin-silver-copper alloy powder and metal particles. Among them, the tin-silver-copper alloy powder refers to a powder made of an alloy synthesized from tin metal, silver metal and copper metal, wherein tin metal is the main component of the tin-silver-copper alloy powder, and the mass proportion of silver metal and copper metal in the tin-silver-copper alloy powder can be determined according to actual conditions, which is not limited in this embodiment. In an implementable manner, the mass proportion of tin metal in the tin-silver-copper alloy powder can reach more than 90%, and the melting point of the tin-silver-copper alloy powder with tin metal as the main component is lower than 450°C, which can be used for soft soldering. The tin-silver-copper alloy powder can be purchased as a commercially available finished product or refined by itself, which is not limited in this embodiment. The metal particles include at least one of silver particles, nickel particles, copper particles, antimony particles, cadmium particles, titanium particles, etc. In one feasible method, the melting point of the metal particles is higher than the melting point of the tin-silver-copper alloy powder, for example, it can be above 260°C. Since the melting point of the metal particles themselves is relatively high, the metal particles themselves will not melt during the second welding process, and the melting through the first welding can enhance the bonding strength between the particles inside the composite solder, thereby effectively improving the melting point of the composite solder. The tin-silver-copper alloy powder in the composite solder powder is mechanically bonded to the metal particles, and the melting point of the composite solder powder is equivalent to that of the tin-silver-copper alloy powder. However, the composite solder melts during the welding process, and the melting process will not change the lattice structure of the tin-silver-copper alloy powder and the metal particles themselves, and will form an interfacial metal copolymer between the tin-silver-copper alloy powder and the metal particles, thereby strengthening the grain boundaries and significantly improving the intermolecular force. Therefore, after the composite solder is melted once, the melting point is greatly increased, by about 17-39°C. The composite solder with an increased melting point will not be completely melted during the second welding process, thereby reducing the risk of component loss and improving the welding reliability of the composite solder in multiple welding processes.

[0024] Exemplarily, the particle size of the tin-silver-copper alloy powder is 15-45 μm.

[0025] The smaller the particle size of the tin-silver-copper alloy powder, the better the fluidity of the tin-silver-copper alloy powder, the smaller the gap between the particles, the faster the heat transfer speed, and the easier it is to fill and weld together during the welding process. The larger the specific surface area, the more grain boundaries, and the larger the grain boundary area, the higher the density and strength of the composite solder at the solder joint formed after welding, and the better the welding quality. However, if the particle size of the tin-silver-copper alloy powder is too small, the repulsive force generated by the friction and collision of the particles will increase, and the fluidity of the tin-silver-copper alloy powder and the bonding force between the particles will decrease. Therefore, the particle size of the tin-silver-copper alloy powder is determined to be in the range of 15-45μm.

[0026] Exemplarily, the tin-silver-copper alloy powder includes at least one of SAC305 alloy powder, SAC0307 alloy powder and SAC387 alloy powder.

[0027] In this embodiment, SAC305 alloy powder refers to an alloy powder containing 96.5% tin, 3% silver and 0.5% copper, SAC0307 alloy powder refers to an alloy powder containing 99% tin, 0.3% silver and 0.7% copper, and SAC387 alloy powder refers to an alloy powder containing 95.5% tin, 3.8% silver and 0.7% copper.

[0028] An appropriate mass proportion of metal particles can improve welding reliability. If the mass proportion of metal particles is small, the strengthening effect is small and the melting point is not significantly improved. If the mass proportion of metal particles is large, it is difficult for the metal particles to completely and tightly combine with the tin-silver-copper alloy powder to form impurities, which will instead cause the uniformity of the composite solder to deteriorate and the welding quality to decrease. Therefore, the mass proportion of metal particles in the composite solder is determined to be 0.5%-20%. For example, the composite solder powder may include 80wt% of tin-silver-copper alloy powder and 20wt% of metal particles, or the composite solder powder may include 90wt% of tin-silver-copper alloy powder and 10wt% of metal particles, or the composite solder powder may include 95wt% of tin-silver-copper alloy powder and 5wt% of metal particles, or the composite solder powder may include 99.5wt% of tin-silver-copper alloy powder and 0.5wt% of metal particles.

[0029] The metal particles added to the composite solder may be one or more types. When multiple types of metal particles are added, the total mass of the various metal particles accounts for 0.5%-20% of the mass of the composite solder powder, for example, 0.5%, 5%, 10%, 20%, etc.

[0030] Exemplarily, the metal particles include at least one of silver particles, nickel particles, and copper particles.

[0031] Silver has a melting point of about 962°C and has excellent electrical conductivity, thermal conductivity and plasticity. When silver particles are added to the composite solder, at the melting point of the tin-silver-copper alloy powder, the silver particles can form an interface metal co-compound of Ag3Sn with the tin-silver-copper alloy powder at the interface, thereby strengthening the grain boundary. Therefore, after the composite solder with silver particles is melted once, the silver particles can still retain their own lattice structure and enhance the bonding force with the tin-silver-copper alloy powder, thereby increasing the melting point. In this way, the composite solder can not be completely melted during the second welding process, reducing the risk of falling parts and improving the welding reliability of the composite solder in multiple welding processes. Adding silver particles to the composite solder can also improve the wettability, fluidity and processing performance of the composite solder. In addition, the tin-silver-copper alloy powder itself contains silver, so the addition of silver particles will not introduce new alloys and will not increase the complexity of the crystal phase.

[0032] The melting point of nickel particles can reach about 1453℃, and they have good mechanical properties, oxidation resistance and corrosion resistance. When nickel particles are added to the composite solder, at the melting point of the tin-nickel-copper alloy powder, the nickel particles can form interface metal co-compounds such as Ni3Sn2, Ni3Sn4, and Ni3Sn7 with the tin-nickel-copper alloy powder at the interface, which strengthens the grain boundary. Therefore, after the composite solder with nickel particles is melted once, the nickel particles can still retain their own lattice structure and enhance the bonding force with the tin-nickel-copper alloy powder, thereby increasing the melting point. As a result, the nickel particles can not be completely melted during the second welding process, reducing the risk of parts falling off and improving the welding reliability of the composite solder in multiple welding processes. Adding nickel particles to the composite solder can also improve the wettability and fluidity of the composite solder.

[0033] The melting point of copper particles can reach about 1358°C, and they have excellent electrical and thermal conductivity. When copper particles are added to the composite solder, at the melting point of the tin-silver-copper alloy powder, the copper particles can form interfacial metal co-compounds such as Cu6Sn5 and Cu3Sn with the tin-silver-copper alloy powder at the interface, thereby strengthening the grain boundary. Therefore, after the composite solder with copper particles is melted once, the copper particles can still retain their own lattice structure and enhance the bonding force with the tin-silver-copper alloy powder, thereby achieving an increase in the melting point, so that they can not be completely melted during the second welding process, reducing the risk of falling parts and improving the welding reliability of the composite solder in multiple welding processes. Adding copper particles to the composite solder can also improve the wettability and fluidity of the composite solder. In addition, the tin-silver-copper alloy powder itself contains copper, so the addition of copper particles will not introduce new alloys and will not increase the complexity of the crystal phase.

[0034] The smaller the particle size of the metal particles, the larger the specific surface area, the more grain boundaries formed between the metal particles and the tin-silver-copper alloy powder, the larger the grain boundary area of ​​the grain boundaries formed between the metal particles and the tin-silver-copper alloy powder, the better the strengthening effect, and the more conducive to the increase of the melting point. However, if the particle size of the metal particles is too small, the strengthening effect will be worse, and the metal particles are easy to dissolve into the tin-silver-copper alloy during the welding process, which will lead to a lower melting point. Due to the different strengths of the interfacial metal compounds formed between different metal particles and the tin-silver-copper alloy powder, the higher the strength of the interfacial metal compounds that can be formed, the lower the addition amount can achieve an increase in the melting point and higher welding quality.

[0035] Exemplarily, the particle size of the silver particles is 0.5-5 μm, and the mass proportion of the silver particles in the composite solder powder is 0.5%-5%.

[0036] In this embodiment, the particle size of the silver particles is in the range of 0.5-5 μm, and the mass proportion of the silver particles in the composite solder powder is 0.5%-5%, for example 0.5%, 1%, 2%, 3%, 4%, 5%, etc., which means that the melting point of the composite solder can be increased by 24-39°C after one melting while ensuring the welding quality. In this way, during the second welding process, the composite solder at the solder joint formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved.

[0037] Exemplarily, the particle size of the nickel particles is 1-3 μm, and the mass proportion of the nickel particles in the composite solder powder is 5%-15%.

[0038] In this embodiment, the particle size of the nickel particles is in the range of 1-3 μm, and the mass proportion of the nickel particles in the composite solder powder is 5%-15%, for example 5%, 8%, 10%, 12%, 15%, etc., which means that the melting point of the composite solder can be increased by 24-37°C after one melting while ensuring the welding quality. In this way, during the second welding process, the composite solder at the weld formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved.

[0039] Exemplarily, the particle size of the copper particles is 5-38 μm, and the mass proportion of the copper particles in the composite solder powder is 10%-20%.

[0040] In this embodiment, the particle size of the copper particles is in the range of 5-38 μm, and the mass proportion of the copper particles in the composite solder powder is 10%-20%, for example 10%, 12%, 15%, 18%, 20%, etc., which means that the melting point of the composite solder can be increased by 17-32°C after one melting while ensuring the welding quality. In this way, during the second welding process, the composite solder at the solder joint formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved.

[0041] In this embodiment, the composite solder includes composite solder powder and solder flux; wherein the composite solder powder includes the following components in terms of mass percentage: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles. During the first welding process, the metal particles in the composite solder at the solder joint formed by the first welding react with the tin-silver-copper alloy powder to form an interface metal co-compound, the grain boundary is strengthened, and a significant strengthening effect is produced. Therefore, after the first welding, the melting point of the composite solder at the solder joint formed by the first welding is greatly improved; on the other hand, the appropriate mass proportion of metal particles can improve welding reliability, the mass proportion of metal particles is small, the strengthening effect is small, and the improvement of melting point is not obvious, the mass proportion of metal particles is large, the metal particles are difficult to disperse, and the bonding tightness between the metal particles and the tin-silver-copper alloy powder is reduced, and impurities are formed, which will lead to the deterioration of the uniformity of the composite solder and the reduction of welding quality. Therefore, the mass proportion of metal particles in the composite solder is determined to be 0.5%-20%. In this way, the melting point of the composite solder after adding metal particles accounting for 0.5%-20% by mass in the composite solder can change after one melting, increasing by about 17-39°C. In this way, during the second welding process, the composite solder at the weld formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved.

[0042] The present application also provides a method for preparing a composite solder, referring to Figure 3 The preparation method of the composite solder is used to prepare the composite solder as above, and the preparation method of the composite solder comprises the following steps:

[0043] Step S10, removing the oxide film on the surface of the metal particles;

[0044] Metal particles are chemically active and easily oxidized, thus forming an oxide film on the surface of the metal particles. The oxide film is hard, dense and chemically inert. The oxide film can effectively prevent the metal particles contained therein from reacting with other external substances. Therefore, it will also prevent the metal particles from reacting with the tin-silver-copper alloy powder, which will reduce the binding force between the metal particles and the tin-silver-copper alloy powder. As a result, the metal particles cannot be tightly combined with the tin-silver-copper alloy powder during the welding process and become refractory impurity components, which cannot provide reinforcement for the tin-silver-copper alloy powder. The melting point of the tin-silver-copper alloy powder will not increase after welding due to the loss of the reinforcement effect of the metal particles. Therefore, before adding metal particles, the oxide film on the surface of the metal particles should be removed first.

[0045] In this embodiment, the outer surface of the metal particles can be processed by physical methods and / or chemical methods to remove the oxide film on the surface of the metal particles, wherein the physical method can be grinding, polishing and the like, and the chemical method can be pickling, electrolysis and the like.

[0046] Exemplarily, the step of removing the oxide film on the surface of the metal particles includes:

[0047] The metal particles are immersed in a dilute nitric acid solution with a volume fraction of 3% to 20% for 3 to 5 minutes to remove the oxide film on the surface of the metal particles.

[0048] In this embodiment, a dilute nitric acid solution can be pre-prepared, and the metal particles are placed in the dilute nitric acid solution and soaked for 3-5 minutes, for example, 3 minutes, 4 minutes, 5 minutes, etc., so that the oxide film on the surface of the metal particles can fully react with the dilute nitric acid solution and be reduced and dissolved under the action of the dilute nitric acid solution. The volume fraction of the dilute nitric acid solution can be 3%-20%, for example, 3%, 10%, 15%, 20%, etc.

[0049] In one practicable manner, after the step of removing the oxide film on the surface of the metal particles, the metal particles may be cleaned with a volatile organic solvent such as ethanol to remove excess dilute nitric acid solution.

[0050] Step S20, mechanically combining the metal particles after the oxide film is removed with the tin-silver-copper alloy powder to obtain a composite solder powder;

[0051] In this embodiment, the metal particles after the oxide film is removed are mixed with the tin-silver-copper alloy powder, and then the metal particles and the tin-silver-copper alloy powder are evenly dispersed under the action of mechanical force and squeezed against each other to be mechanically combined together to obtain a composite solder powder. The mechanical combination method can make the metal particles and the tin-silver-copper alloy powder evenly distributed, which is beneficial to improve the uniformity of the metal particles strengthening the tin-silver-copper alloy powder during the first melting.

[0052] Exemplarily, the step of mechanically combining the metal particles after the oxide film is removed with the tin-silver-copper alloy powder to obtain the composite solder powder includes:

[0053] The metal particles after the oxide film is removed are kneaded with the tin-silver-copper alloy powder for 30-50 minutes to mechanically combine the metal particles with the tin-silver-copper alloy powder to obtain a composite solder powder.

[0054] In this embodiment, the metal particles after the oxide film is removed and the tin-silver-copper alloy powder are added to a kneader, and the metal particles and the tin-silver-copper alloy powder are squeezed against each other under the action of mechanical force by the kneader, and kneaded for 30-50 minutes, for example, 30 minutes, 40 minutes, 50 minutes, etc., so that the metal particles and the tin-silver-copper alloy powder are mechanically combined together to obtain a composite solder powder.

[0055] Step S30, mixing the composite solder powder with the solder flux to obtain a composite solder.

[0056] In this embodiment, a solder flux is added to the prepared composite solder powder and mixed evenly. In an practicable manner, a solder paste mixer may be used to stir for 5-30 minutes to obtain the composite solder.

[0057] In an practicable manner, after the step of mixing the composite solder powder with the solder flux to obtain the composite solder, the method may further include: storing the composite solder at a temperature of 2-10° C. after filling.

[0058] In this embodiment, after removing the oxide film from the metal particles, the metal particles are mechanically combined with the tin-silver-copper alloy powder, and then mixed with the solder flux to obtain a composite solder with a variable melting point, and the preparation method is simple. By adding metal particles that retain their own lattice structure as reinforcements to the composite solder powder, the composite solder still has a melting point comparable to that of the tin-silver-copper alloy powder without the addition of metal particles before welding, but after welding, due to the metal particles and the tin-silver-copper alloy powder undergoing a metallurgical reaction during the first welding, an interfacial metal co-compound is formed, the grain boundaries are strengthened, and the intermolecular forces are significantly improved, and the melting point can be increased by about 17-39°C. The composite solder after the melting point is increased will not be completely melted during the second welding process, thereby reducing the risk of parts falling off and improving the welding reliability of the composite solder in multiple welding processes.

[0059] The preparation method of the composite solder provided in the present application solves the technical problem of low welding reliability of the composite solder used for soldering in conventional technology. Compared with conventional technology, the beneficial effects of the preparation method of the composite solder provided in the embodiment of the present application are the same as the beneficial effects of the composite solder provided in the above embodiment, and other technical features in the preparation method of the composite solder are the same as the features disclosed in the above embodiment method, which will not be repeated here.

[0060] In order to better illustrate the technical solutions of the embodiments of the present application, the composite solder and the preparation method of the composite solder provided by the present application are further explained in combination with several embodiments below.

[0061] Example 1

[0062] Raw materials: Tin-silver-copper alloy powder is SAC305, No. 3 powder (particle size 25-45μm), the soft soldering agent is the soft soldering agent matching SAC305, and the metal particles are 0.5μm silver particles.

[0063] Preparation method:

[0064] Weigh 4.65 g of silver particles, 88.35 g of SAC305, and 7 g of solder;

[0065] Put the silver particles into 3% dilute nitric acid, soak for 5 minutes, wash with appropriate amount of alcohol and dry for later use;

[0066] The SAC305 and silver particles were added into a kneader and kneaded for 30 minutes to obtain a composite solder powder of SAC305 reinforced with silver particles;

[0067] The soft solder and the composite solder powder were added into a mixer and stirred for 5 minutes to obtain a composite solder with a variable melting point of 5 wt % silver particles reinforced SAC305.

[0068] Example 2

[0069] Raw materials: Tin-silver-copper alloy powder is SAC305, No. 4 powder (particle size 20-38μm), the solder flux is the solder flux matching SAC305, and the metal particles are 5μm silver particles.

[0070] Preparation method:

[0071] Weigh 0.44 g of silver particles, 87.56 g of SAC305, and 12 g of solder flux;

[0072] Put the silver particles into 20% dilute nitric acid, soak for 3 minutes, wash with appropriate amount of alcohol and dry for later use;

[0073] The SAC305 and the silver particles were added into a kneader and kneaded for 50 minutes to obtain a composite solder powder of SAC305 reinforced with silver particles;

[0074] The soft solder and the composite solder powder were added into a mixer and stirred for 30 minutes to obtain a composite solder with a variable melting point of 0.5 wt % silver particles reinforced SAC305.

[0075] Example 3

[0076] Raw materials: Tin-silver-copper alloy powder is SAC305, No. 5 powder (particle size 15-25μm), the soft soldering agent is the soft soldering agent matching SAC305, and the metal particles are 3μm silver particles.

[0077] Preparation method:

[0078] Weigh 2.55 g of silver particles, 82.45 g of SAC305, and 15 g of solder flux;

[0079] Put the silver particles into 10% dilute nitric acid, soak for 4 minutes, wash with appropriate amount of alcohol and dry for later use;

[0080] The SAC305 and silver particles were added into a kneader and kneaded for 40 minutes to obtain a composite solder powder of SAC305 reinforced with silver particles;

[0081] The soft solder and the composite solder powder were added into a mixer and stirred for 15 minutes to obtain a composite solder with a variable melting point of 3 wt % silver particles reinforced SAC305.

[0082] Example 4

[0083] Raw materials: Tin-silver-copper alloy powder is SAC0307, ​​No. 3 powder (particle size 25-45μm), the soft soldering agent is the soft soldering agent matching SAC0307, ​​and the metal particles are 5μm copper particles.

[0084] Preparation method:

[0085] Weigh 9.3g of copper particles, 83.7g of SAC0307, ​​and 7g of solder flux;

[0086] Put the copper particles into 3% dilute nitric acid, soak for 5 minutes, wash with appropriate amount of alcohol and dry for later use;

[0087] The SAC0307 and copper particles were added into a kneader and kneaded for 30 minutes to obtain a composite solder powder of SAC0307 reinforced with copper particles;

[0088] The soft solder and the composite solder powder were added into a mixer and stirred for 5 minutes to obtain a composite solder with a variable melting point of 10 wt % copper particles reinforced SAC0307.

[0089] Example 5

[0090] Raw materials: Tin-silver-copper alloy powder is SAC0307, ​​No. 4 powder (particle size 20-38μm), the soft soldering agent is the soft soldering agent matching SAC0307, ​​and the metal particles are 38μm copper particles.

[0091] Preparation method:

[0092] Weigh 17g of copper particles, 68g of SAC0307, ​​and 15g of solder flux;

[0093] Put the copper particles into 20% dilute nitric acid, soak for 3 minutes, wash with appropriate amount of alcohol and dry for later use;

[0094] The SAC0307 and copper particles were added into a kneader and kneaded for 50 minutes to obtain a composite solder powder of SAC0307 reinforced with copper particles;

[0095] The soft solder and the composite solder powder were added into a mixer and stirred for 30 minutes to obtain a composite solder with a variable melting point of 20 wt % copper particles reinforced SAC0307.

[0096] Example 6

[0097] Raw materials: Tin-silver-copper alloy powder is SAC0307, ​​No. 5 powder (particle size 15-25μm), the soft soldering agent is the soft soldering agent matching SAC0307, ​​and the metal particles are 20μm copper particles.

[0098] Preparation method:

[0099] Weigh 12.75 g of copper particles, 72.25 g of SAC0307, ​​and 15 g of solder flux;

[0100] Put the copper particles into 10% dilute nitric acid, soak for 4 minutes, wash with appropriate amount of alcohol and dry for later use;

[0101] The SAC0307 and copper particles were added into a kneader and kneaded for 40 minutes to obtain a composite solder powder of SAC0307 reinforced with copper particles;

[0102] The soft solder and composite solder powder were added into a mixer and stirred for 15 minutes to obtain a composite solder with a variable melting point of 15 wt % copper particles reinforced SAC0307.

[0103] Example 7

[0104] Raw materials: Tin-silver-copper alloy powder is SAC387, No. 3 powder (particle size 25-45μm), the soft soldering agent is the soft soldering agent matching SAC387, and the metal particles are 1μm nickel particles.

[0105] Preparation method:

[0106] Weigh 4.25 g of nickel particles, 80.75 g of SAC387, and 15 g of solder flux;

[0107] Put the nickel particles into 3% dilute nitric acid, soak for 3 minutes, wash with appropriate amount of alcohol and dry for later use;

[0108] The SAC387 and nickel particles were added into a kneader and kneaded for 30 minutes to obtain a composite solder powder of SAC387 reinforced with nickel particles;

[0109] The soft solder flux and the composite solder powder were added into a mixer and stirred for 5 minutes to obtain a composite solder with a variable melting point of 5 wt % nickel particles reinforced SAC387.

[0110] Example 8

[0111] Raw materials: Tin-silver-copper alloy powder is SAC387, No. 4 powder (particle size 20-38μm), the soft soldering agent is the soft soldering agent matching SAC387, and the metal particles are 3μm nickel particles.

[0112] Preparation method:

[0113] Weigh 13.05 g of nickel particles, 73.95 g of SAC387, and 13 g of solder flux;

[0114] Put the nickel particles into 20% dilute nitric acid, soak for 5 minutes, wash with appropriate amount of alcohol and dry for later use;

[0115] The SAC387 and nickel particles were added into a kneader and kneaded for 50 minutes to obtain a composite solder powder of SAC387 reinforced with nickel particles;

[0116] The soft solder and the composite solder powder were added into a mixer and stirred for 30 minutes to obtain a composite solder with a variable melting point of SAC387 reinforced with 15 wt % nickel particles.

[0117] Example 9

[0118] Raw materials: Tin-silver-copper alloy powder is SAC387, No. 5 powder (particle size 15-25μm), the soft soldering agent is the soft soldering agent matching SAC387, and the metal particles are 2μm nickel particles.

[0119] Preparation method:

[0120] Weigh 9.3 g of nickel particles, 83.7 g of SAC387, and 7 g of solder flux;

[0121] Put the nickel particles into 10% dilute nitric acid, soak for 4 minutes, wash with appropriate amount of alcohol and dry for later use;

[0122] The SAC387 and nickel particles were added into a kneader and kneaded for 40 minutes to obtain a composite solder powder of SAC387 reinforced with nickel particles;

[0123] The soft solder and composite solder powder were added into a mixer and stirred for 15 minutes to obtain a composite solder with a variable melting point of SAC387 reinforced with 10 wt % nickel particles.

[0124] Comparative Example 1

[0125] Commercially available SAC305 no-clean solder paste, No. 4 powder (particle size 20-38μm).

[0126] Comparative Example 2

[0127] Commercially available SAC0307 no-clean solder paste, No. 4 powder (particle size 20-38μm).

[0128] Comparative Example 3

[0129] Commercially available SAC387 no-clean solder paste, No. 4 powder (particle size 20-38μm).

[0130] Performance Testing

[0131] The melting point test of the composite solder prepared in Examples 1-9 and Comparative Examples 1-3 is performed below. The composite solder prepared in Examples 1-9 and Comparative Examples 1-3 is melted for the first time, and the melting point of the first melting is tested. After cooling, the composite solder is melted for the second time, and the melting point of the second melting is tested. The test results are shown in Table 1:

[0132] Table 1

[0133]

[0134] It can be seen from Table 1 that, compared with the comparative example, after adding metal particles, in Examples 1-9, during the first melting process, the melting point is equivalent to that before adding metal particles, and after the first melting, the melting point increases by about 17-39°C. In this way, during the second welding process, the composite solder at the weld point formed by the first welding will not be completely melted. Therefore, the risk of falling parts can be reduced and the welding reliability of the composite solder in multiple welding processes can be improved.

[0135] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A composite solder, characterized in that: The composite solder comprises composite solder powder and solder flux; The composite solder powder comprises the following components in terms of mass percentage: 80%-99.5% of tin-silver-copper alloy powder and 0.5%-20% of metal particles.

2. The composite solder according to claim 1, characterized in that: The mass proportion of the composite solder powder in the composite solder is 85%-93%, and the mass proportion of the soft solder in the composite solder is 7%-15%.

3. The composite solder according to claim 1, characterized in that: The metal particles include at least one of silver particles, nickel particles and copper particles.

4. The composite solder according to claim 3, characterized in that: The particle size of the silver particles is 0.5-5 μm, and the mass proportion of the silver particles in the composite solder powder is 0.5%-5%.

5. The composite solder according to claim 3, characterized in that: The particle size of the nickel particles is 1-3 μm, and the mass proportion of the nickel particles in the composite solder powder is 5%-15%.

6. The composite solder according to claim 3, characterized in that: The copper particles have a particle size of 5-38 μm, and the mass proportion of the copper particles in the composite solder powder is 10%-20%.

7. The composite solder according to claim 1, characterized in that: The particle size of the tin-silver-copper alloy powder is 15-45 μm.

8. The composite solder according to claim 1, characterized in that: The tin-silver-copper alloy powder includes at least one of SAC305 alloy powder, SAC0307 alloy powder and SAC387 alloy powder.

9. A method for preparing a composite solder, characterized in that: The method for preparing the composite solder is used to prepare the composite solder according to any one of claims 1 to 8, and the method for preparing the composite solder comprises the following steps: Remove the oxide film on the surface of metal particles; Mechanically combining the metal particles after the oxide film is removed with tin-silver-copper alloy powder to obtain composite solder powder; The composite solder powder is mixed with a soft solder agent to obtain a composite solder.

10. The method for preparing the composite solder according to claim 9, characterized in that: The step of removing the oxide film on the surface of the metal particles comprises: The metal particles are immersed in a dilute nitric acid solution with a volume fraction of 3% to 20% for 3 to 5 minutes to remove the oxide film on the surface of the metal particles.

11. The method for preparing the composite solder according to claim 9, characterized in that: The step of mechanically combining the metal particles after the oxide film is removed with the tin-silver-copper alloy powder to obtain the composite solder powder comprises: The metal particles after the oxide film is removed are kneaded with the tin-silver-copper alloy powder for 30-50 minutes to mechanically combine the metal particles with the tin-silver-copper alloy powder to obtain composite solder powder.